Exodus of Clinicians from Public Sector to Non-Clinical Practice in Private Sector in Dar es Salaam Tanzania; Exploring the Drivers (Tanzania Medical Journal, 2020)
Background: Globally, shortage of clinicians health workforce is among the major challenges facing the health systems of many countries including Tanzania. Migration of medical doctors from clinical practice to non-clinical practice partly contributes to this challenge. This study aimed to explore factors influencing Medical Doctors’ decision to migrate from clinical practice in the public sector to non-clinical practice in the private sector in Dar es Salaam Tanzania.Methods: An exploratory qualitative study was conducted using 12 in-depth interviews with medical doctors working in the private sector but formerly worked in the public health sector. Interviews were digitally recorded, transcribed verbatim and thematically analyzed.Results: Three main themes emerged; health system-level drivers that has three sub-themes, namely poor work environment, heavy workload due to shortage of clinicians and underfunded public health sector; individual-level drivers, which include four sub-themes: Age, area of specialization, marital status and empathy to patients; and external environment drivers consisting of two sub-themes: peer pressure and community culture.Conclusion: Improving the work environment through increased funding will partly address the main health system drivers underlying migration from the clinical practice. Furthermore, nurturing junior doctors to be enthusiastic and adapting to cultural shocks can partly help to address the individual and external drivers. Keywords: Shortage, Medical Doctors, Clinicians, Physicians, migration, health workforce, Tanzania Clinical Practice, Non-Clinical Practice.